Alternative Design of Steel-Based Approach Structure for Pedestrian Suspension Bridge: A Case Study in Lobang Baru Village, Indonesia - Ruspiansyah; M. Firdaus; Agung Pranata (Indonesian Journal Publisher, 2025)
This research investigates an alternative structural design for the approach bridge of a pedestrian suspension bridge by replacing reinforced concrete with structural steel to address construction challenges in remote areas. The study focuses on the Lobang Baru Pedestrian Suspension Bridge in Banjar Regency, South Kalimantan, where the Kulur Tengah side faces significant logistical constraints including limited accessibility, frequent river flooding, and inadequate transportation infrastructure for concrete materials. Using finite element modeling analysis, two structural systems were comprehensively evaluated: the existing reinforced concrete design and a proposed steel-based alternative. The steel alternative design employs H-shaped steel sections for main girders (H350x350-12/19), diaphragms (H200x200-8/12), and cross girders (H300x300-10/15), with hollow structural sections (HSS 508x9.5) for columns and 8mm steel deck plates. Results demonstrate substantial improvements: total structural weight decreased by 72.2% from 55.92 tons to 15.55 tons, with the weight per unit length reduced from 3.43 ton/m to 0.65 ton/m. The steel design eliminated 23.79 m³ of concrete from the superstructure while requiring only a single support at the pillar block instead of dual supports at both pillar and anchor blocks, thereby reducing structural complexity and foundation loads. Although substructure concrete volume increased by 27.12 m³ due to the separate abutment construction, the overall design significantly improves constructability through prefabrication, modular assembly, and reduced vulnerability to environmental conditions. These findings validate the technical and practical feasibility of steel-based approach structures for pedestrian suspension bridges in challenging rural environments, offering a replicable solution for similar infrastructure projects across Indonesia and other developing regions facing comparable geographic and climatic constraints.